Dyadic interactions in children exhibiting the broader autism phenotype: Is the broader autism phenotype distinguishable from typical development?. Issue 3 (9th January 2019) - Kellerman, A. M.; Schwichtenberg, A. J.; Tonnsen, B. L.; Posada, G.; Lane, S. P.
Abstract : In families raising a child with an autism spectrum disorder (ASD), infant siblings are at elevated risk for ASD and other developmental concerns, including elements of the broader autism phenotype (BAP). Typically, the BAP is indexed using standardized developmental assessments; however, these measures do not capture a number of social difficulties commonly associated with the BAP. The present study aims to expand our developmental understanding of the BAP by comparing children exhibiting the BAP to their typically developing peers on, (a) standardized measures of development, and (b) social behaviors exhibited during dyadic play interactions. As part of a prospective study, dyads were recruited from families with at least one older child with ASD (high‐risk, n = 36), and families with no history of ASD (low‐risk, n = 38). During laboratory visits at 12, 15, 18, and 24 months of age, infants completed a series of standardized assessments and a mother–child play interaction. Dyadic play interactions were micro‐analytically coded for gaze, positive affect, and vocalizations to create theory‐driven composites to index dyadic synchrony and responsiveness. Videos were also coded with an existing rating scheme for joint engagement and child responsiveness. Multilevel models revealed significant group differences on select constructs within the first 2 years. Language and cognitive differences emerged by 24 months of age, whereas dyadic differences were evident as early as 15 months. Recognizing the increasing demand for elevated‐risk interventions, these findings highlight several social constructs through which interventions may identify risk and promote optimal development. Autism Res 2019, 12: 469–481 © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: In families raising children with an autism spectrum disorder (ASD), younger siblings are at an increased risk for social and developmental difficulties that characterize a "broader autism phenotype." The present study explored the emergence of social, language, and cognitive differences in the first 2 years of life. Social differences were evident as early as 15 months of age for several play‐based measures, and language and cognitive differences emerged by 24 months of age. For infant siblings of children with ASD, some of the earliest behavioral marks for subclinical features of ASD are evident within the first 2 years of life.